Production and characterization of antioxidative peptides during lactic fermentation of goat milk. Issue 12 (3rd October 2021) - Panchal, Gaurav Kumar; Das, Sujit; Sakure, Amar; Singh, Brij Pal; Hati, Subrota
Abstract: In the study, Lactobacillus fermentum M2 was characterized with potent antioxidative properties viz. ABTS assay (57.09%), HFRSA (57.30%), and SFRSA (51.40%) after 48 hr at 37°C in fermented goat milk. Further, the inoculation rate (2%) and incubation time (48 hr) for the production of peptides were also optimized using proteolytic activity at 37°C during the fermentation of goat milk. The molecular weight of proteins was analyzed by SDS‐PAGE and protein bands in the range of 10–51 kDa were found. The 2D gel electrophoresis exhibited 41 protein spots between 10 and 51 kDa. The trypsin digested protein spots were injected into RPLC/MS for amino acid sequencing. The 3 and 10 kDa permeate fragments were injected into RPLC/MS for characterization of peptides, and the peptide masses from LC/MS were analyzed on MASCOT. Novel antioxidative peptides viz., SCQDQPTTLAR (2D‐PAGE), TIDMESTEVFTKK (3 kDa Permeate), and YIQKEDVPSER (10 kDa Permeate) were identified from goat milk fermented with M2 by matching with BLASTp (NCBI), protein information resource (PIR), and BIOPEP databases. Practical applications: Goat milk provides several health benefits, including antioxidative, antihypertensive, and antimicrobial properties. In terms of bio‐functional characteristics, goat milk fermented with healthy lactic acid bacteria could even add more value. Goat milk fermented with Lactobacillus fermentum M2 exhibited promising bioactivities like hydroxyl free radical scavenging assay, superoxide free radical scavenging assay, antioxidative activity, and proteolytic activities. A few novel antioxidative peptides, viz., SCQDQPTTLAR, TIDMESTEVFTKK, and YIQKEDVPSER, were identified from goat milk fermented with M2 by similarity searches using BLASTp, PIR, and BIOPEP databases. Furthermore, L . fermentum M2 could be used for the production of fermented goat milk with antioxidative activity and bioactive peptides.